A randomised controlled trial of laser scanning and casting for the construction of ankle foot orthoses - Roberts, Andrew; Wales, Johanna; Smith, Heather; Sampson, Christopher James; Jones, Peter; James, Marilyn (International Society for Prosthetics and Orthotics International, 2014)
Study Design: Randomised controlled trial with blinding of orthotists and patients to the construction technique used. Background: Three-dimensional laser scanning has been used for patient measurement for cranial helmets and spinal braces. Ankle foot orthoses are commonly prescribed for children with orthopaedic conditions. This trial sought to compare ankle foot orthoses produced by laser scanning or traditional plaster casting. Objectives: Assessment of the effectiveness and efficiency of using laser scanning to produce AFOs. Methods: A randomised double blind trial comparing fabrication of AFOs from casts or laser scans. Results: The time spent in the rectification and moulding of scanned AFOs was around 50% less than for cast AFOs. A non-significant increase of 9 days was seen in the time to delivery to the patient for LSCAD/CAM. There was a higher incidence of problems with the scan-based AFOs at delivery of the device, but no difference in how long the AFOs lasted. Costs associated with laser scanning were not significantly different from traditional methods of AFO manufacture. Conclusions: Compared with conventional casting techniques laser scan based AFO manufacture neither significantly improved the quality of the final product nor delivered a useful saving in time.